2021
DOI: 10.1080/14740338.2021.1915279
|View full text |Cite
|
Sign up to set email alerts
|

Vitiligo induced by immune checkpoint inhibitors in melanoma patients: an expert opinion

Abstract: Introduction: Treatment with immune checkpoint inhibitors in melanoma patients can cause immunerelated adverse effects, such as vitiligo. In vitiligo, specific autoimmunity against melanocytes results in depigmentation of the skin. Melanoma-associated vitiligo occurring in melanoma patients treated with immune checkpoint inhibitors can be seen as a good prognostic sign as higher survival rates in melanoma-associated vitiligo cases have been reported.Areas covered: This review gives an insight into the pathophy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 39 publications
0
32
0
Order By: Relevance
“…On the other hand, autoimmunity may also have a protective role. In fact, patients undergoing an autoimmune reaction against melanocytes, such as vitiligo patients, show either a lower risk of developing melanoma [ 27 , 28 ] or a better prognosis [ 29 , 30 ], most likely due to a so-called “beneficial autoimmunity” [ 31 ]. The present study investigated the hypothesis that the expression of genes directly involved in autoimmunity may be altered in melanoma patients and may therefore represent suitable molecular targets for possible diagnostic, prognostic or therapeutic applications.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, autoimmunity may also have a protective role. In fact, patients undergoing an autoimmune reaction against melanocytes, such as vitiligo patients, show either a lower risk of developing melanoma [ 27 , 28 ] or a better prognosis [ 29 , 30 ], most likely due to a so-called “beneficial autoimmunity” [ 31 ]. The present study investigated the hypothesis that the expression of genes directly involved in autoimmunity may be altered in melanoma patients and may therefore represent suitable molecular targets for possible diagnostic, prognostic or therapeutic applications.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it happens that impaired function of T reg in the skin leads to the formation of T RM cells with autoimmune activity. To confirm this hypothesis, it was observed that the checkpoint inhibitor therapy used in patients with melanoma is associated with an increase in vitiligo disease (169,225).…”
Section: T Rm Cells and Autoimmune Diseasementioning
confidence: 98%
“…Vitiligo is caused by destruction of melanocytes and is characterized by well-defined, hypopigmented macules that often coalesce into patches. 3,69 Vitiligo occurs in up to 16% of patients with melanoma, either Violaceous/erythematous, pruritic papules and plaques 19 Innate immune system activation leading to a Th1 response. 48 Decreased Tregs 48 Lichenoid reactions have also been reported in response to proton pump inhibitors, b-blockers and anti-TNF-a agents 47 Psoriasiform reactions ~4% of all cutaneous irAEs 50 Well-demarcated, scaly, erythematous plaques 22 Increased expression of IL-17 secondary to alteration of Th1 and Th17 pathways.…”
Section: Melanocyte Changesmentioning
confidence: 99%
“…65 Upregulation of C1r/C1s and TLR 4 (innate immune system) 67 All reported cases of BP irAE have been in patients treated with PD-(L) 1 inhibitors. 63 BP has also been reported in response to DPP-4 inhibitors, spironolactone and furosemide 99 Vitiligo ICI-associated and/or spontaneous vitiligo observed in up to 16% of patients with melanoma 70 Well-defined, hypopigmented macules that often coalesce into patches 69 Increased CXCR3 and CXCL10. 74 Tissue-resident memory T cells.…”
Section: Melanocyte Changesmentioning
confidence: 99%